The Contribution of Romidepsin to the Herbicidal Activity of Burkholderia rinojensis Biopesticide - Owens, Daniel K.; Bajsa-Hirschel, Joanna; Duke, Stephen O.; Carbonari, Caio A. [UNESP]; Gomes, Giovanna L. G. C. [UNESP]; Asolkar, Ratnakar; Boddy, Louis; Dayan, Franck E. (Amer Chemical Soc, 2020)
The culture broth of Burkholderia rinojensis strain A396 is herbicidal to a number of weed species with greater observed efficacy against broadleaf than grass weeds. A portion of this activity is attributed to romidepsin, a 16-membered cyclic depsipeptide bridged by a 15-membered macrocyclic disulfide. Romidepsin, which is present in small amounts in the broth (18 to 25 mu g mL(-1)), was isolated and purified using standard chromatographic techniques. It was established that romidepsin is a natural proherbicide that targets the activity of plant histone deacetylases (HDAC). Assays to measure plant HDAC activity were optimized by testing a number of HDAC substrates. The activity of romidepsin was greater when its macrocyclic-forming disulfide bridge was reduced to liberate a highly reactive free butenyl thiol side chain. Reduction was achieved using 200 mM tris(2-carboxyethyl)phosphine hydrochloride. A similar bioactivation of the proherbicide via reduction of the disulfide bridge of romidepsin was observed in plant-cell-free extracts. Molecular dynamic simulation of the binding of romidepsin to Arabidopsis thaliana HDAC19 indicated the reduced form of the compound could reach deep inside the catalytic domain and interact with an associated zinc atom required for enzyme activity.